Moderasi Beragama dalam Tafsir Nusantara: Analisis Tematik Nilai-Nilai Toleransi dalam Marah Labid Karya Syekh Nawawi Al-Bantani - Puji Astuti; Fiddian Khairudin; Amaruddin Amaruddin (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2026)
The discourse on religious moderation often creates tension between classical texts perceived as rigid and contemporary pluralistic realities. This study aims to deconstruct and thematically classify moderation values in the book “Marah Labid” by Syekh Nawawi Al-Bantani, an authoritative 19th-century Indonesian commentator. Utilizing a qualitative library research method, this study applies the “Maudhu’i” (Thematic) interpretation approach integrated with intertextual and linguistic analysis. Primary data were extracted from the “Marah Labid” text, while secondary data were obtained from relevant hermeneutic and religious moderation literature. Research findings indicate that Syekh Nawawi constructed a “Nusantara Moderation” pattern through the reconstruction of meanings in key verses such as QS. Al-Baqarah: 256, QS. Al-Hujurat: 13, and QS. Al-Mumtahanah: 8. Linguistic analysis reveals that the sentence structures in the interpretation emphasize human autonomy in faith and the obligation of distributive justice across faiths. Intertextually, Syekh Nawawi deconstructed the “naskh” status of tolerance verses and positioned them as “muhkam” (permanent) verses.